USE OF ARTILLERY FIRE SUPPORT ASSETS IN THE ATTRITION APPROACH IN THE RUSSIA-UKRAINE CONFLICT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The armed conflict between Russia and Ukraine since February 24, 2022 does not appear to have a clear end, but to trace the possible paths of development, a better understanding of the strategy of waging war by the armed forces of both countries is needed. More detail on the attrition approach would facilitate realistic estimates of the duration of military conflict and the likely costs of artillery systems and munitions used in it. The causes and aspects of the implementation of exhaustion and its relationship with the amount of artillery ammunition used, develop the direct dependence on the increased need for their use. The influence of post-Soviet fire support assets on the different combat use procedures applied by the Ukrainian forces and the provision of Western-style weapons of varying types and quantities indicate the reasons for the implementation of the attrition strategies. The use of the artillery systems according to the stock method and the available amount of ammunition for them leads to the impossibility of applying their capabilities in a full profile on the battlefield to achieve the goals set by the political demands.